The Application of Restorative Justice Principles in the Indonesian Criminal Justice System as an Alternative to Punishment - Januri Januri; Mirwansyah Mirwansyah; Irwan Jaya Diwirya (Journal of Social Science and Humanities, 2025)
This study examines the persistent limitations of retributive punishment within the Indonesian criminal justice system, particularly its inability to fully address victim needs, offender accountability, and social restoration. The objective of the research is to analyze the application of restorative justice principles as an alternative to conventional punishment and to assess their normative legitimacy, practical implementation, and implications for criminal law reform in Indonesia. The research subjects consist of primary and secondary legal materials, including legislation, institutional regulations, court decisions, and scholarly works relevant to restorative justice and criminal justice reform, which were selected purposively based on relevance and authority. Employing a qualitative normative legal research approach, data were collected through systematic document study and literature review, supported by statutory, conceptual, and comparative legal analyses. The data were analyzed using qualitative legal interpretation to identify patterns, coherence, and gaps in the application of restorative justice principles. The findings reveal that restorative justice has contributed to a paradigm shift in criminal case resolution by emphasizing harm restoration, victim participation, and offender reintegration, particularly at the investigation and prosecution stages. However, its implementation remains fragmented and largely dependent on discretionary policies rather than comprehensive statutory regulation. The study concludes that restorative justice represents a legitimate and transformative alternative to punishment that can strengthen the humanistic orientation of criminal law while enhancing social justice and legal responsiveness. Its application has important implications for the development of a more balanced, inclusive, and socially grounded criminal justice system in Indonesia.